Consumer behaviour towards mobile advertising during National Recovery Plan - Wong, Shi Hui (2022)
This study attempts to identify the factors affecting the effectiveness of mobile advertising on consumers’ purchase intention. Besides, the present research also aims to develop a research model based on the S-O-R model that could identify the factors that influence the effectiveness of mobile advertising. The last objective to achieve is to analyse the factors used in the proposed research framework. Therefore, Stimulus-Organism-Response (SOR) Model and Theory of Reasoned Action (TRA) have been used to accomplish the three objectives. There are nine variables investigated in the research framework and eight hypotheses have been established. Among the nine variables, seven of them are independent variables which are attractiveness, trustworthiness, expertise, social presence, user interface, product price, and product usefulness. Then, one of the variables is the mediator, consumers’ purchase intention and the dependent variable, consumer buying behaviour. Primary data collection is applied by distributing 200 questionnaires to respondents in Malaysia. Besides, IBM SPSS Statistics is used to analyse on the data collected and the results are presented in table form. Lastly, the implications, limitations and suggestions are being discussed in the final chapter. This research is contributing theoretically to the scholar and future research, and contributing to the industry players. However, this study is lack of investigation on consumers in different phases and sampling bias occurs. There are suggestions recommended to the future researchers on relevant topics.